SECURITIES CROWDFUNDING TEROBOSAN BARU PADA HUKUM PASAR MODAL DI INDONESIA - Tan, Kendry (UNIB Press, 2024)
As a member of the global economy, Indonesia is experiencing the fourth industrial revolution. The rise of the fourth industrial revolution has had both beneficial and negative effects on Indonesian society, particularly on MSMEs. MSMEs must constantly grow and strengthen their capabilities in order to thrive in the era of the Fourth Industrial Revolution. As a result, the government of Indonesia adopted a Securities Crowdfunding policy to aid the growth of MSMEs. Researchers undertake research using a legislative and conceptual approach related to the topic at hand. According to the findings of study, Securities Crowdfunding is a government program aimed at improving Indonesia's economic underpinnings. It plays a vital role in implementing securities crowd funding and provides significant benefits to the existence and growth of MSMEs in Indonesia.